PENGGUNAAN FAN-N-PICK SEBAGAI PENUNJANG MOTIVASI BELAJAR DAN PENGUASAAN KOSA KATA BAHASA INGGRIS - Rini Yudiati; Ach. Andriyanto (Universitas Al-Amien Prenduan, 2017)
The purpose of this study was to improve vocabulary mastery and learning motivation on students using the Fan-n-Pick method. This study used classroom action research, which was conducted in two cycles, each cycle consisting of three meetings and each cycle covering four stages. The stages in this research include: planning, implementing, observing and reflecting. The subjects of this study were the eighth grade students of SMP Yas'a, Sumenep Regency, which consisted of 20 students. The data collection techniques used were tests, questionnaires, observations and interviews. The data analysis technique used is quantitative descriptive analysis technique. The results showed that students' motivation in the learning process increased from the first cycle of 65.65% to 91.30% in the second cycle there was an increase of 25.65%, and from the results of the student questionnaire 67% in the first cycle to 89% in the second cycle increased. 12.00%. Student learning outcomes on the final test or on daily tests have increased the percentage of students completing learning in the initial conditions 35.00% to 60.00% in cycle I means an increase of 25.00% and to 90.00% in cycle II up 30.00 %. The class average score also increased from the initial condition of 57.50 to 70.00 in the first cycle, up 12.50 points and to 81.75 in the second cycle, up 11.75 points. Thus the learning atmosphere is more attractive, students are more active, can increase student motivation and student learning outcomes increase.